2018
DOI: 10.1108/jica-09-2017-0029
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of joint specialist case conferences for building general practice capacity to enhance diabetes care

Abstract: Purpose Type 2 diabetes mellitus has become a major concern of Australian healthcare providers. From rates of barely more than 1 percent in the mid-90s, diabetes is now the leading cause of morbidity in the country. To combat the growing diabetes epidemic, Western Sydney Local Health District created the Western Sydney Diabetes (WSD) initiative. One of the key components of the WSD initiative since 2014 has been joint specialist case conferencing (JSCC). The purpose of this paper is to evaluate the JSCC servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…Joint Specialist Case Conferencing comprises of an integrated discussion about a patients’ diabetes management between the diabetes specialist, resident, diabetes educator, patient and primary care physician and is carried out in the primary care clinic for 30-min consultations per patient. We have previously shown that JSCC lead to benefits after a single visit to primary care physicians, including an absolute reduction of − 0.87% in HbA1c and reductions in blood pressure, lipid profile and weight, and that the results were durable to 3-years [21].…”
Section: Discussionmentioning
confidence: 99%
“…Joint Specialist Case Conferencing comprises of an integrated discussion about a patients’ diabetes management between the diabetes specialist, resident, diabetes educator, patient and primary care physician and is carried out in the primary care clinic for 30-min consultations per patient. We have previously shown that JSCC lead to benefits after a single visit to primary care physicians, including an absolute reduction of − 0.87% in HbA1c and reductions in blood pressure, lipid profile and weight, and that the results were durable to 3-years [21].…”
Section: Discussionmentioning
confidence: 99%
“…In western Sydney, successful Integrated Care initiatives have been progressively incorporated into today’s co‐commissioning models of care. These include: specialist rapid access clinics for patient stabilisation and general practitioner support, demonstrating a 32% reduction in emergency department presentations and a 34% reduction in admissions; 11 diabetes outreach to general practice via specialist case conferencing, demonstrating enhancement in general practice team capability and patient clinical outcomes; 12 and non‐prescribing pharmacists in general practices providing measurable change or deprescribing in complex care patients 13 …”
Section: One State’s Reform Experiencementioning
confidence: 99%
“…Cases discussed were those with significant hyperglycaemia (HbA1c ≥9%, 75 mmol/mol), uncertain diagnoses, wider metabolic issues and where next management steps were uncertain. The "patientfree" approach has previously been used in England [16] and it differs from the patient present approach used elsewhere [17]. HealthPathways is an online referral guidelines portal used by health professionals at the point of care to plan patient care, and where necessary, provide information on how to refer to specialists and other services [18].…”
Section: Case Conferencingmentioning
confidence: 99%
“…Joint specialist and general practitioner case conference evaluations in Western Sydney and Hunter and New England have been associated with improvements in clinical parameters such as Haemoglobin A1c, Body Mass Index and blood pressure of patients. They have high program acceptability from both general practitioners and patients [17,31]. Such Australian integrated diabetes care approaches, along with the Beacon model (diabetes care within general practice supported by an endocrinologist, credentialed diabetes educator and delivered by advanced skill general practitioners) show that better glycaemic control is achievable through a more integrated approach between general practitioners and specialist care [32].…”
Section: Engage Regularly With the Local Healthcare Professionals Fromentioning
confidence: 99%